Association of hypometabolism and amyloid levels in aging, normal subjects - Lowe, Val J; Weigand, Stephen D; Senjem, Matthew L; Vemuri, Prashanthi; Jordan, Lennon; Kantarci, Kejal; Boeve, Bradley; Jack, Jr, Clifford R; Knopman, David; Petersen, Ronald C (Neurology, 2014)
We evaluated the relationship of amyloid, seen on Pittsburgh compound B (PiB)-PET, and metabolism, seen on [(18)F]-fluorodeoxyglucose (FDG)-PET, in normal subjects to better understand pathogenesis and biomarker selection in presymptomatic subjects. Normal participants (aged 70-95 years; 600 with PiB-PET, FDG-PET, and MRI) were included. We performed a cross-sectional evaluation and subcategorized participants into amyloid-negative (<1.4), high-normal (1.4-1.5), positive (1.5-2.0), and markedly positive (>2.0) PiB standardized uptake value ratio groups representing different levels of amyloid brain load. Associations with metabolism were assessed in each group. Relationships with APOE ε4 carriage were evaluated. Hypometabolism in "Alzheimer disease (AD)-signature" regions was strongly associated with PiB load. Hypometabolism was greater with more positive PiB levels. Additional, more-diffuse cortical hypometabolism was also found to be associated with PiB, although less so. No hypermetabolism was seen in any subset. No significant incremental hypometabolism was seen in APOE-positive vs -negative subjects. Hypometabolism in PiB-positive, cognitively normal subjects in a population-based cohort occurs in AD-signature cortical regions and to a lesser extent in other cortical regions. It is more pronounced with higher amyloid load and supports a dose-dependent association. The effect of APOE ε4 carriage in this group of subjects does not appear to modify their hypometabolic "AD-like" neurodegeneration. Consideration of hypometabolism associated with amyloid load may aid trials of AD drug therapy.